IMPLEMENTASI NILAI-NILAI KEPEMIMPINAN DEMOKRATIS DALAM FILM “SANG KYAI” - Donny Dwi Setiabudi, Donny Dwi Setiabudi (LPPM Stikosa-AWS, 2024)
One of the determinants of an organization's success can be determined by the way a leader directs his organization. This method can be done by choosing an appropriate leadership style to give authority or encouragement to others, such as a democratic leadership style. This study aims to provide an overview of the implementation of democratic leadership values reflected in the film